Beyond biomarkers: designer natriuretic peptides and cGMP centered therapies for cardiorenal and cardiometabolic protection in chronic heart failure - Ivan Isaia; Giulia Cevoli; Reza Parvan; Horng H. Chen; Alessandro Cataliotti; John C. Burnett; Lorenzo Malatino (Internal and Emergency Medicine, 2026)
Abstract Chronic heart failure (CHF) remains a leading cause of morbidity and mortality worldwide, despite the improvement in guideline-directed medical therapy (GDMT). Natriuretic peptides (NPs), originally identified as diagnostic and prognostic biomarkers of HF, are now recognized as important regulators of cardiovascular, renal and metabolic homeostasis. The NP system, including atrial (ANP), B-type (BNP), and C-type (CNP) NPs, exerts protective effects through activation of particulate guanylyl cyclase receptors and, downstream, cyclic guanosine monophosphate (cGMP) signalling, thereby promoting natriuresis, vasodilation, anti-fibrotic and anti-inflammatory actions. In CHF, however, the effectiveness of this endogenous system is reduced, due to impaired NP bioactivity together with counter-regulatory neurohormonal activation, a phenomenon commonly referred to as “natriuretic peptide resistance”. Recent advances in peptide engineering have enabled the development of novel designer NPs, including Cenderitide, aimed at restoring and enhancing their signalling. As a dual GC-A/GC-B dual-receptor agonist, Cenderitide represents a prototype of this approach, integrating renal-enhancing and anti-fibrotic effects while minimizing systemic haemodynamic perturbations. Additional engineered peptides, including ANX042, MANP, and CRRL269, as well as complementary approaches targeting the cGMP pathway, such as soluble guanylate cyclase (sGC) stimulators, neprilysin inhibitors, and GC-A positive allosteric modulators, are further expanding the therapeutic potential of NP-centred therapies. Beyond cardiovascular effects, NPs also influence metabolic regulation and renal function, highlighting their relevance in cardiometabolic disease. Collectively, these developments support a shift from the use of NPs solely as biomarkers toward their emerging role as therapeutic targets and agents in the treatment of CHF.